Farmed fish as a functional food: Perception of fish fortification and the influence of origin - Insights from Portugal - Ribeiro, Ana Ramalho (2020)
Being a rich source of important nutrients, including highly digestible proteins, vitamins (A, D3), trace minerals (iodine, selenium) and n-3 long chain polyunsaturated fatty acids (n-3 LCPUFA), fish consumption is generally regarded as part of a healthy dietary pattern. Exogenous feeding in aquaculture unlocks the possibility to tailor fish composition with healthy valuable nutrients. However, the use of supplements in the fish feed during fish production may undermine consumers' perception opinion of these fortified products. The effectiveness success of a functional food is a combination of its efficacy and meeting consumers' expectations. A self-administered questionnaire was designed to assess consumers' preferences regarding fish consumption, and their perception of farmed seabream as a functional food. A high consumption rate of fish, (between daily, and a minimum of three times a week), was reported by 47% of the respondents. Freshness, flavour, quality and price were the four most valued attributes. Good acceptance of the fish fortification concept was observed (53%), as well as positive receptiveness to its consumption (50%). Anti-oxidants and omega-3 fatty acids were the most accepted compounds for fish fortification. Additionally, two consumer groups were established based on their high (HIG) or low (LIG) interest in fish origin (wild vs aquaculture). The LIG was more receptive to all aspects of fish fortification and showed willingness to buy and consume it. This suggests that fortified fish could be targeted to the LIG profile group, which represents 42% of the studied population. With appropriate communication, farmed fish may be a good candidate for functional food.